Facial attractiveness and lip morphology of Caucasian women - Lewandowski, Zdzisław; Danel, Dariusz P. (Anthropological Review, 2018)
Human lips are one of the most sexually dimorphic facial features. Although lip morphology is considered particularly important for female facial attractiveness no systematic empirical study has been conducted in this respect. This study aimed to investigate a relationship between female Caucasian facial attractiveness and their lip morphology. Two series of morphologically average composite portraits with digitally increased and decreased lip width and height measurements were assessed by adult men and women. Results were analysed using repeated measures ANOVA. When compared to the average lip shape both a decrease and an increase in lip width were associated with lower female facial attractiveness. A systematic increase in lip height from the lowest values to the highest, was associated with an increase in attractiveness scores. Attractiveness assessments of men and women did not differ significantly. The results show that perception of lip attractiveness may be intersexually congruent and that a variation in lip morphology may significantly affect female facial attractiveness.